Value Change: More and More Germans Showing a Postmaterialistic Orientation - Martin Kroh (Weekly Report, 2008)
A popular theory of value change states that "postmaterialistic" values such as emancipation and personal development are steadily replacing traditional "materialistic" values such as social advancement and economic security as a result of the ongoing improvement of living conditions since the Second World War. Post-materialism is thus seen as a phenomenon directly linked to economic affluence. Based on the Socio-Economic Panel data, it can be shown that between 1986 and 2006, the percentage of individuals displaying a postmaterialistic value orientation has risen among West Germans. Surprisingly, East Germans have become distinctly more postmaterialistic in the last ten years, and have virtually reached the West German level. In general, each generation tends to be somewhat more postmaterialistic than the one before. Particularly postmaterialistic population groups are the self-employed, people with a high level of education, and Alliance 90/Green Party supporters. An analysis of value orientations within families shows that adult siblings display strong similarities to one another with regard to their values, which suggests a process of value formation taking place during childhood and adolescence. The results also show that it is not the economic situation in parental households but rather the parents' value orientations that most crucially shape their children's values.
Keywords: Z13; D72; C23; 330; Value change; Postmaterialism; Intergenerational transmission